Ethiopia’s Regional States Assessment for Belg 2022 Season and Climate Outlook for the Kiremt 2022 Season - Teshome, Asaminew; Tesfaye, Kindie; Demissie, Teferi Dejene (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
The eleven regional meteorological services centers under EMI, has been generating and disseminating consensus based user relevant seasonal climate outlook products in real time to reduce climate related risks and support sustainable development for the coming season in sectors of critical socioeconomic significances for their region. The RMSCs typically has been held tri-annual seasonal climate outlook forums where regional representatives from sectors like agriculture, health, water and disaster risk reduction gather to review the previous seasons climate performance and the likelihood of the upcoming seasons climate outlook and its implication on the most pertinent socioeconomic sectors in the given region.